2g=-5+3g

Simple and best practice solution for 2g=-5+3g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2g=-5+3g equation:



2g=-5+3g
We move all terms to the left:
2g-(-5+3g)=0
We add all the numbers together, and all the variables
2g-(3g-5)=0
We get rid of parentheses
2g-3g+5=0
We add all the numbers together, and all the variables
-1g+5=0
We move all terms containing g to the left, all other terms to the right
-g=-5
g=-5/-1
g=+5

You can always share this solution

See similar equations:

| 15d+20=110 | | -9u=-8u+7 | | x-25=18;= | | 15j=2+14 | | 4p=2p-8 | | 21=z?53 | | 50=z+-4 | | E^-x=245 | | d+87=-8 | | 1.5t^2+4.9t+2=0 | | 4(-8x-12)=-26-32x | | -3x+7-6(x-1)=-(2x-4)-6x+6 | | b^2+5=17 | | z?-41=54 | | 4u-36=6(u-5) | | d?698=-271 | | -216=-6(1-5r) | | x-4-15=10 | | -7y+2(y-2)=31 | | 7(n=4)21 | | 3(-4-6b)=114 | | 181=84-w | | -140=5(4a-4) | | k-875=-750 | | y=4×5+12 | | k?875=-750 | | -8q=-88 | | -m+8(5-8m)=300 | | -3t=-78 | | 6x-4(3-2x)=4(x-4)-36 | | 41=6g+5 | | -8=w/8 |

Equations solver categories